Analysis of Wear Resistance in Eco-Friendly Paving Blocks Utilizing Multilayer Aluminum–LDPE Plastic Waste - Nani Mulyaningsih; Sri Hastuti; Hanafi Izzul; Bagas Tri (Mechanical Engineering Department - Semarang State Polytechnic, 2026)
The growing demand for sustainable construction materials has encouraged research on the utilization of multilayer aluminum plastic waste and low-density polyethylene (LDPE) waste as substitution materials in the production of paving blocks. This study emphasizes abrasion resistance as a key indicator of paving block quality. The waste materials were processed through melting and subsequently blended with fine aggregates of sand and combustion ash in varying compositions. The abrasion resistance value obtained was 0.0771 mm/min, which corresponded to the Class B quality standard as specified in SNI 03-0691-1996. The results demonstrate that incorporating multilayer aluminum plastic and LDPE waste at a proportion of 65% enhances the abrasion resistance of paving blocks compared to conventional ones. This improvement is attributed to the plasticity of LDPE, which increases flexibility and reduces microcracking, as well as the contribution of aluminum layers that provide greater resistance to friction. Further analysis suggests that paving blocks incorporating multilayer aluminum plastic and LDPE waste are suitable for use in residential roads, village pathways, and office yards subject to moderate vehicle traffic. These findings support the notion that integrating multilayer aluminum plastic waste into construction materials not only improves the technical performance of the product but also offers a strategic solution to reduce the accumulation of non-biodegradable waste.